2006
DOI: 10.1124/jpet.106.101998
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive and Hypothermic Effects of Salvinorin A Are Abolished in a Novel Strain of κ-Opioid Receptor-1 Knockout Mice

Abstract: Salvia divinorum is a natural occurring hallucinogen that is traditionally used by the Mazatec Indians of central Mexico. The diterpene salvinorin A was identified as an active component of S. divinorum over 20 years ago, but only recently has biochemical screening indicated that a molecular target of salvinorin A in vitro is the -opioid receptor. We have examined whether salvinorin A, the C2-substituted derivative salvinorinyl-2-propionate, and salvinorin B can act as -opioid receptor agonists in vivo. We fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
88
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(97 citation statements)
references
References 35 publications
(45 reference statements)
5
88
0
3
Order By: Relevance
“…The observation that two axon extension markers were down-regulated in KOR-null spinal cord would suggest a functional role for KOR in EGF-stimulated axon extension. This was tested by using primary DRG neurons obtained from normal and KOR-null mutant mice (16), as well as normal and KOR-silenced primary rat DRG neurons. As shown in Fig.…”
Section: Kor and Its Ligands Are Required For Egf-stimulated Axon Extmentioning
confidence: 99%
See 1 more Smart Citation
“…The observation that two axon extension markers were down-regulated in KOR-null spinal cord would suggest a functional role for KOR in EGF-stimulated axon extension. This was tested by using primary DRG neurons obtained from normal and KOR-null mutant mice (16), as well as normal and KOR-silenced primary rat DRG neurons. As shown in Fig.…”
Section: Kor and Its Ligands Are Required For Egf-stimulated Axon Extmentioning
confidence: 99%
“…To determine the physiological function of KOR in the developing nervous system, we conducted preliminary experiments using primary DRG neurons dissected from the wild-type (WT) and KOR-null animals (16) to examine several developmental parameters and the sensitivity of the dissected DRG cultures to stimulation by potential growth factors. Preliminary experiments suggested that, in developing embryos, KOR could play a functional role in neurite extension, particularly in response to EGF stimulation.…”
mentioning
confidence: 99%
“…To overcome this limitation, a new set of receptor and ligand was recently developed [152,153]. KORD, the new DREADD, is a kappa-opioid receptor coupled to inhibitory Gi protein and selectively responsive to an inert ligand, salvinorin B [153][154][155]. With 2 chemogenetic tools, the same circuit can be manipulated bidirectionally, activating or inactivating, with different ligands.…”
Section: Designer Receptor Exclusively Activated By Designer Drugmentioning
confidence: 99%
“…Esta substância parece ser "alucinógeno por excelência" (Valdes, 1994), produzindo efeitos psicotrópicos apenas pela estimulação do receptor opióide kappa (González et al, 2006;Prisinzano, 2005;Babu et al, 2008), com afinidade muito pouco significativa pelos receptores opióides mu (Wang et al, 2004;Rothman et al, 2007) e kappa do tipo 2 (Ansonoff et al, 2006) e sem ação sobre receptores serotoninérgicos do tipo 2A (González et al, 2006;Prisinzano, 2005;Babu et al, 2008).…”
Section: Revisãounclassified
“…A ativação de KOP in vivo causa analgesia, disforia, elevação corticoesteróide, diurese (Wang et al, 2004;Lee et al, 2005) e hipotermia (Ansonoff et al, 2006), porém não determina depressão respiratória (Babu et al, 2008).…”
Section: Mecanismo De Ação Da Salvinorina a E Relação Com Potencial Dunclassified